2009
DOI: 10.1007/s11239-009-0330-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of modes of prothrombin time reporting in patients with advanced liver disease associated with viral hepatitis

Abstract: we conclude that, in patients with liver disease, only activity percentage expression may provide a common international scale of PT reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…PTA was calculated using PT, which is a method of normalizing PT values. A previous report 16 has shown that PTA is the most suitable expression form of PT in patients with advanced viral hepatitis. In our study, most patients (83.3%) had hepatitis B virus infection.…”
Section: Discussionmentioning
confidence: 95%